The complete mitochondrial genome of Oxyopes hupingensis (Araneae: Oxyopidae): characterization and phylogenetic analysis. Issue 1 (2nd January 2019) - Yang, Wen-Jia; Xu, Kang-Kang; Yang, Da-Xing; Li, Can
Abstract: The complete mitochondrial genome of the lynx spider Oxyopes hupingensis was characterized in this study. The circular genome is 15, 078 bp in length (GenBank accession number MK518391), containing 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA genes, and a control region. Its gene direction and arrangement are identical to those of other spider mitogenomes. The overall base composition is 34.76% A, 43.11% T, 8.04% C, and 14.09% G, showing AT-rich feature (77.87%). Ten PCGs are initiated with typical ATN start codons, three genes ( cox2, cox3, and nad4 ) begin with TTG. Nine PCGs stop with complete termination codon TAA and TAG, cox1, nad4, nad4L, and cob are terminated with T. Twenty-three reading frame overlaps and four intergenic regions were found in the mitogenome of O. hupingensis. Three tRNAs lack the dihydrouracil (DHU) arm, whereas eight tRNAs lose the TΨC arm stems. Phylogenetic tree based on concatenated amino acid sequences of 13 PCGs shows that O. hupingensis has a close phylogenetic relationship with Oxyopes sertatus and belongs to Oxyopidae.